Chronic Glucocorticoid-Rich Milieu and Liver Dysfunction. (11th August 2016) - Villagarcía, Hernán Gonzalo; Sabugo, Vanesa; Castro, María Cecilia; Schinella, Guillermo; Castrogiovanni, Daniel; Spinedi, Eduardo; Massa, María Laura; Francini, Flavio
Abstract : We investigated the impact of chronic hypercorticosteronemia (due to neonatal monosodium L-glutamate, MSG, and treatment) on liver oxidative stress (OS), inflammation, and carbohydrate/lipid metabolism in adult male rats. We evaluated the peripheral concentrations of several metabolic and OS markers and insulin resistance indexes. In liver we assessed (a) OS (GSH and protein carbonyl groups) and inflammatory ( IL-1b, TNFa, and PAI-1 ) biomarkers and (b) carbohydrate and lipid metabolisms. MSG rats displayed degenerated optic nerves, hypophagia, low body and liver weights, and enlarged adipose tissue mass; higher peripheral levels of glucose, triglycerides, insulin, uric acid, leptin, corticosterone, transaminases and TBARS, and peripheral and liver insulin resistance; elevated liver OS, inflammation markers, and glucokinase (mRNA/activity) and fructokinase (mRNA). Additionally, MSG liver phosphofructokinase-2, glucose-6-phosphatase (mRNA and activity) and glucose-6-phosphate dehydrogenase, Chrebp, Srebp1c, fatty acid synthase, and glycerol-3-phosphate (mRNAs) were increased. In conclusion adult MSG rats developed an insulin-resistant state and increased OS and serious hepatic dysfunction characterized by inflammation and metabolic signs suggesting increased lipogenesis. These features, shared by both metabolic and Cushing's syndrome human phenotypes, support that a chronic glucocorticoid-rich endogenous environment mainly impacts on hepatic glucose cycle, displacing local metabolism to lipogenesis. Whether correcting the glucocorticoid-rich environment ameliorates such dysfunctions requires further investigation.